2020
DOI: 10.3390/ani10010113
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Use of a Qualitative Behavioural Assessment Approach to Assess Emotional State of Calves in Rodeos

Abstract: There are longstanding disagreements between the rodeo industry stakeholders and animal welfare advocates about the wellbeing of the animals used in events. The current study aims to determine whether qualitative behavioural assessment (QBA) is effective in identifying the emotional state of calves in so-called calf-roping events. Still images of calves captured from videos of calf-roping were shown to two groups: practitioners (n = 7) and students (n = 16). For each image, they scored (on a scale of 1–10) 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Results of the current study could have been strengthened through use of a combination of positive welfare indicators. For example, correlates of enhanced affective states have been demonstrated between QBA results and ear position in calves and lambs (98,99) and QBA and positive social behaviour in dairy cows (46). Divergences may also highlight where studies making reference to changes in affective states require further replication or validation.…”
Section: Qba and Study Limitationsmentioning
confidence: 99%
“…Results of the current study could have been strengthened through use of a combination of positive welfare indicators. For example, correlates of enhanced affective states have been demonstrated between QBA results and ear position in calves and lambs (98,99) and QBA and positive social behaviour in dairy cows (46). Divergences may also highlight where studies making reference to changes in affective states require further replication or validation.…”
Section: Qba and Study Limitationsmentioning
confidence: 99%
“…Scoring animal demeanour could be considered fundamentally similar to this, capturing what a good stockperson does when they survey their livestock in a formal, numerical manner (Fleming et al, 2016). The application of including demeanour to feedlots is novel; however, the full QBA approach has been validated in cattle under numerous contexts (see; Rousing and Wemelsfelder, 2006;Brscic et al, 2010;Stockman et al, 2013;de Boyer des Roches et al, 2018;Vindevoghel et al, 2019;Rizzuto et al, 2020), with the modified-QBA (demeanour) approach recently reported useful and valid for welfare assessment within the Australian live export industry (Willis et al, 2021a;Willis et al, 2021b). At feedlots, demeanour may provide evidence of positive affective state, and an early indicator of issues, such as thermal stress, ill-health, and unstable social housing, allowing earlier mitigation than otherwise would be possible.…”
Section: Proposed Measures To Address 'Appropriate Behaviour'mentioning
confidence: 99%
“…Three different aspects of the tail are thought to be important in various species; tail position, tail movement and laterality of tail movement. For cattle a raised or tucked tail may indicate fear (Goma et al, 2018;Rizzuto et al, 2020), but as far as we know there is no study investigating the association between tail position and positive emotions in cattle. There are some indications that tail movement, e.g., wagging, may be associated with pleasurable activities (brushing and feeding; de Oliveira and Keeling, 2018).…”
Section: Tail Positionmentioning
confidence: 99%